Corn Price Volatility in The World Market - Wijayati, Prasmita Dian; Rachmadhan, Aditya Arief; Rizkiyah, Noor (JSEP (Journal of Social and Agricultural Economics), 2024)
Corn is one of the food commodities traded globally as food, feed and biofuel commodities. Global demand for corn will tend to increase from year to year considering the multifunctional uses of corn. Climate change also take part in decreasing global production. Producer countries, namely China, America, and Brazil, suffered severe drought in 2020. It had impact in global corn market since the low of production. Globally, corn is used as food, but Indonesia imports corn as feed. Therefore, the price of corn in the global market is of concern to the Indonesian government. Fluctuations alone are not enough to describe the movement of corn prices, it is necessary to do a volatility analysis to find out how much uncertainty corn prices are in the global market. This study aims to determine the volatility of corn prices in the world market. The data used is secondary data obtained from the World Bank's Pink Sheet Data from 1960 to 2020. This study uses the econometric method using the ARIMA (Autoregressive Integrated Moving Average) and ARCH GARCH (Autoregressive Conditional Heteroscedasticity-Generalized Autoregressive Conditional Heteroscedasticity) model. The results showed that corn prices were volatile most of the year from 1960 to 2020.